2004
DOI: 10.1111/j.1939-165x.2004.tb00378.x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of free and total cyst(e)ine in plasma of dogs and cats

Abstract: These results emphasize the importance of removing plasma proteins within 1 hour after blood collection for reliable assay of free plasma cyst(e)ine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…In the present study it was unfortunately not possible to meaningful assess the cats’ cyst(e)ine status because the low plasma/serum cyst(e)ine concentrations noted in all cats were likely artefactual, due to cysteine interaction with sulphydryl groups on plasma proteins and subsequent loss when the protein was precipitated during sample preparation. This loss occurs rapidly in feline plasma/serum that is not deproteinised immediately after collection [29]. …”
Section: Discussionmentioning
confidence: 99%
“…In the present study it was unfortunately not possible to meaningful assess the cats’ cyst(e)ine status because the low plasma/serum cyst(e)ine concentrations noted in all cats were likely artefactual, due to cysteine interaction with sulphydryl groups on plasma proteins and subsequent loss when the protein was precipitated during sample preparation. This loss occurs rapidly in feline plasma/serum that is not deproteinised immediately after collection [29]. …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that methionine is susceptible to oxidation during storage [30], whilst cysteine is unstable in storage if samples are not deproteinised by treating with sulphosalicylic acid immediately after sampling [31]. Given that the storage conditions of the current study were not optimized for either amino acid, we were concerned that results would not be reliable and, therefore, chose not to analyse them.…”
Section: Discussionmentioning
confidence: 99%
“…Methionine was not measured because previous studies have demonstrated that this amino acid is susceptible to oxidation during storage [30]. Cysteine was also not measured because this amino acid is susceptible to breakdown if not treated with sulfosalicylic acid immediately after sampling [31]. …”
Section: Methodsmentioning
confidence: 99%
“…The LP diet was made by adding additional fat, pregelatinised starch, minerals and vitamins to a moist commercial diet (which had passed a minimum feeding protocol for proving an adult maintenance claim for a cat food (11) ), in order to reduce the protein content ( Table 1). After a 9 d period during which the animals adapted to the metabolism cages (days 1-9), urine was collected quantitatively for 5 d (days [10][11][12][13][14] and pooled per cat. Thereafter, the cats received the moist HP diet (Table 1) for a further 9 d (days 15-23) before urine was again collected for 5 d (days [24][25][26][27][28] and pooled per cat.…”
Section: Animals and Housingmentioning
confidence: 99%